Comparison of two multilocus sequence based genotyping schemes for Leptospira species. - Ahmed Ahmed; Janjira Thaipadungpanit; Siriphan Boonsilp; Vanaporn Wuthiekanun; Kishore Nalam; Brian G Spratt; David M Aanensen; Lee D Smythe; Niyaz Ahmed; Edward J Feil; Rudy A Hartskeerl; Sharon J Peacock (PLoS Neglected Tropical Diseases)
Background Several sequence based genotyping schemes have been developed for Leptospira spp. The objective of this study was to genotype a collection of clinical and reference isolates using the two most commonly used schemes and compare and contrast the results. Methods and findings A total of 48 isolates consisting of L. interrogans (n = 40) and L. kirschneri (n = 8) were typed by the 7 locus MLST scheme described by Thaipadungpanit et al., and the 6 locus genotyping scheme described by Ahmed et al., (termed 7L and 6L, respectively). Two L. interrogans isolates were not typed using 6L because of a deletion of three nucleotides in lipL32. The remaining 46 isolates were resolved into 21 sequence types (STs) by 7L, and 30 genotypes by 6L. Overall nucleotide diversity (based on concatenated sequence) was 3.6% and 2.3% for 7L and 6L, respectively. The D value (discriminatory ability) of 7L and 6L were comparable, i.e. 92.0 (95% CI 87.5-96.5) vs. 93.5 (95% CI 88.6-98.4). The dN/dS ratios calculated for each locus indicated that none were under positive selection. Neighbor joining trees were reconstructed based on the concatenated sequences for each scheme. Both trees showed two distinct groups corresponding to L. interrogans and L. kirschneri, and both identified two clones containing 10 and 7 clinical isolates, respectively. There were six instances in which 6L split single STs as defined by 7L into closely related clusters. We noted two discrepancies between the trees in which the genetic relatedness between two pairs of strains were more closely related by 7L than by 6L. Conclusions This genetic analysis indicates that the two schemes are comparable. We discuss their practical advantages and disadvantages.